Eksterna ekonomija i disekonomija u investicijama prometne infrastrukture - Šimulčik, Damir (Promet - Traffic&Transportation, 2012)
Traffic infrastructure as an inseparable segment of community and business life takes an important position in the sphere of a harmonious development of all segments of the social reproduction process. This means that a harmonious development in the area of a rational and economic investment activity including traffic infrastructure facilities must inevitably take heed of the effects of the external economy and external diseconomy. In this the traffic infrastructure facilities develop into the elements of harmonious relationships in the process of the investment activity, which must not and absolutely cannot be unilateral. The complex aspect of viewing both positive and negative effects is a distinctive quality of each and every rational investment activity, because it is an accepted fact that there exists no such activity which yields only positive effects. These investment activities oriented towards traffic infrastructure facilities in the community and business systems must arise from more complex reviews and verified methods for the final effects to incorporate all the elements of a harmonious relationship of positive and negative effects of a concrete investment operation. The paper deals with respective effects and indispensable coordination of external economy and external diseconomy, which has been regarded in the up-to-date processes of the investment activity as only a marginal problem, present yet not worth deeper reviewing. .By gradual dehumanization of the environment coming as a result of an uneconomical and inadequately controlled investment activity i.e. advance exploitation of the resources of future generations, we face a problem which no longer has a restricted effect but has already metastasized into all cells of life and has been faking daily its gigantic toll.